PENERJEMAHAN TEKS SASTRA DAN BUDAYA - Wijaya, Iriany Kesuma (JURNAL TARBAWIYAH, 2015)
Translation is the process of transferring a message from the source language into the target language by considering the range of matching and text. In the transfer of messages, a translator must master the source language and the various texts to be translated. McGuire stated that